Estado nutricional y desarrollo psicomotor en niños de 3-5 años de la Escuela 18 de noviembre de la ciudad de Loja en el periodo marzo-agosto del 2016. - Cartuche Cajamarca, Enith Yakeline (2017)
Alterations in nutritional status can have serious consequences on the development of children. Motivated in this reality, this descriptive, prospective, cross- sectional study was carried out in the period March-August 2016 in children from 3 to 5 years of 18 de Noviembre school of the city of Loja, with the purpose of knowing the nutritional status, evaluating the psychomotor development and establishing the relationship that exists between these two variables. A sample of 135 preschool children of both genders was analyzed in which they obtained the anthropometric data of weight and height with which the body mass index (BMI) was identified. These were entered into the WHO software, WHO ANTHRO to calculate the corresponding standard deviation. At that same time, each child was given the Denver II test to evaluate psychomotor development, with 3.07% (n = 5) being overweight and 2.22% (n = 3) being obese. Regarding development, 1.48% (n = 2) had an abnormal psychomotor development, specifically in the area of fine motor. When relating nutritional status and psychomotor development, it was identified that children who had abnormalities in their development had an adequate nutritional status. Also, overweight children showed normal psychomotor development, it is possible to point out that the developmental alterations identified in this study were not associated with nutritional status. Key words: nutritional status, body mass index (BMI), psychomotor development, Denver.